If 3x+y+z=0 then show that 27x^3+y^3+z^3=9xyz
Answers
Answered by
6
3x+y+z=0=> 3x+y = -z On cubing on both sides, we get =>
![{(x + y)}^{3} = {x}^{3} + {y}^{3} + 3xy(x + y) {(x + y)}^{3} = {x}^{3} + {y}^{3} + 3xy(x + y)](https://tex.z-dn.net/?f=+%7B%28x+%2B+y%29%7D%5E%7B3%7D+%3D++%7Bx%7D%5E%7B3%7D+++%2B++%7By%7D%5E%7B3%7D++%2B+3xy%28x+%2B+y%29)
![{(3x + y)}^{3} = { - z}^{3} = > {(3x)}^{3} + {y}^{3} + {(3x + y)}^{3} = { - z}^{3} = > {(3x)}^{3} + {y}^{3} +](https://tex.z-dn.net/?f=+%7B%283x+%2B+y%29%7D%5E%7B3%7D++%3D++%7B+-+z%7D%5E%7B3%7D+%3D++%26gt%3B++%7B%283x%29%7D%5E%7B3%7D++%2B++%7By%7D%5E%7B3%7D+++%2B)
![3(3x)(y)(3x + y) = > 27 {x}^{3} + {y}^{3} + {z}^{3} = 3(3x)(y)(3x + y) = > 27 {x}^{3} + {y}^{3} + {z}^{3} =](https://tex.z-dn.net/?f=3%283x%29%28y%29%283x+%2B+y%29+%3D++%26gt%3B+27+%7Bx%7D%5E%7B3%7D+%2B++%7By%7D%5E%7B3%7D+%2B++%7Bz%7D%5E%7B3%7D+%3D+++)
![= - 9xy(3x + y) = > 27 {x}^{3} + {y}^{3} + {z}^{3} = - 9xy(3x + y) = > 27 {x}^{3} + {y}^{3} + {z}^{3}](https://tex.z-dn.net/?f=+%3D++-+9xy%283x+%2B+y%29+%3D++%26gt%3B+27+%7Bx%7D%5E%7B3%7D++%2B++%7By%7D%5E%7B3%7D+%2B++%7Bz%7D%5E%7B3%7D++)
![so \: 27 {x}^{3} + {y}^{3} + {z}^{3} = 9xyz so \: 27 {x}^{3} + {y}^{3} + {z}^{3} = 9xyz](https://tex.z-dn.net/?f=so+%5C%3A+27+%7Bx%7D%5E%7B3%7D+%2B++%7By%7D%5E%7B3%7D+%2B++%7Bz%7D%5E%7B3%7D++++%3D+9xyz)
Hence showed .
Hence showed .
Answered by
5
3x+y+z=0
3x+y=-z
=(3x+y)³=-z³
= 27x³+y³+9xy(3x+y)=-z³
= 27x³+y³+9xy(-z)=-z³. [ (3x+y)=-z]
= 27x³+y³-9xyz=-z³
= 27x³ +y³ +z³ = 9xyz
Hence proved
3x+y=-z
=(3x+y)³=-z³
= 27x³+y³+9xy(3x+y)=-z³
= 27x³+y³+9xy(-z)=-z³. [ (3x+y)=-z]
= 27x³+y³-9xyz=-z³
= 27x³ +y³ +z³ = 9xyz
Hence proved
Similar questions